An Instrument for Assessing the Development of Scientific Imagination via Digital Storytelling for Elementary School Students. Issue 4 (2nd October 2019) - Chuang, Hsueh-Hua; Hsieh, Ming-Hung; Cheng, Ying-Yao; Wang, Chia-Chi
Abstract : This study established indicators for the development of scientific imagination (SI) via digital storytelling (DS) and developed and validated a scale for DS-based scientific imagination (DSSI) to understand how it develops in elementary school students. Two samples of fourth- to sixth-grade students in Taiwan participated in a development test, one for item revision and the other for validation. Samples 1 and 2 included 303 and 806 students, respectively. DSSI indicators were constructed based on assessments of SI constructs and its three stages, as well as the framework and rubrics of e-learning DS. Then a DSSI instrument was developed with five dimensions: brainstorming, dynamic adjustment, virtual practise, practise, and presentation. Item analyses were conducted to confirm multiple validities through two-stage sampling via Rasch analyses. The five constructs showed good model fit. Thus, all items were found to be suitable for examining the five dimensions, which provided the validity of the content and structure. Regarding generalizability, the results of the DSSI instrument did not differ by gender. However, student ability was lower than the item difficulty in the five dimensions, indicating that they had reached only a low level of DSSI ability. Pedagogical implications and directions for future research are discussed.